THE USE OF GRAPHIC ORGANIZERS TO IMPROVE STUDENTS’ WRITING SKILL OF JUNIOR HIGH SCHOOL - Berlidio Rizky Agasi (English Education Department Slamet Riyadi University Surakarta, 2018)
The objectives of this research are (1) to find out whether Graphic Organizers can improve writing skill of Eight Grade students of SMP N 4 Sukoharjo in 2017/ 2018Academic Year (2) to find out how is the class condition when Graphic Organizers is implemented in writing class at Eight Grade of SMP N 4 Sukoharjo in 2017/2018Academic Year. This researcher held from January 2017 to January 2018. In this research, the researcher conducted two cycles. Each cycle consisted of two meetings and one posttest. Each cycle had four steps: planning, action, observation, and reflection. In collecting the data, the researcher used observation, interview, document, and test. In analyzing the data, the researcher used quantitative and qualitative data analysis. The researcher conducted pre-test, post-test 1 and post-test 2 to get raw data. After the researcher had the data, the researcher calculated the mean score from the pretest, post test1 and posttest 2. The researcher also calculated t-value using t-test. The result of this research shows that there was improvement in students’ writing skill. Based on the mean score of the students in pre-test was 19,34, meanwhile in the post-test I of cycle I, it increased to 60,5. In the post-test II of cycle II the value had increased to average value 72,9. Besides, the class condition was better where the students’ enthusiasm was increased to learn English. The students were able to transform their idea into written form using graphic organizers. Based on the result above, it can be concluded that (1) Graphic Organizers strategy can improve students’ writing skill in class VIII G of SMP Negeri 4 Sukoharjo in2017/2018 Academic Year and (2) class condition was better after the implementation of Graphic Organizers strategy. Graphic Organizers strategy can be new way in teaching learning to improve students’ writing skill.